Functional magnetic resonance imaging providing the brain effect mechanism of acupuncture and moxibustion treatment for depression - Wong, Kelvin K. L.; Xu, Jinping; Chen, Cang; Ghista, Dhanjoo; Zhao, Hong (Frontiers in Neurology, 2023)
The efficacy of acupuncture and moxibustion in the treatment of depression has been fully recognized internationally. However, its central mechanism is still not developed into a unified standard, and it is generally believed that by regulating the cortical striatum thalamic neural pathway of the limbic system. In recent years, some scholars have applied functional magnetic resonance imaging (fMRI) to study the central mechanism and associated brain effects of acupuncture and moxibustion treatment for depression. reviews the acupuncture and moxibustion treatment of depression from two aspects: (1) fMRI study of brain function related to acupuncture treatment of depression: different acupuncture and moxibustion methods are summarized, the fMRI technique is elaborately explained, and the results of fMRI study on the effects of acupuncture are analyzed in detail; (2) fMRI associated ‘brain functional network’ effects of acupuncture and moxibustion on depression, including the effects on hippocampus, amygdala, cingulate gyrus, frontal lobe, temporal lobe and other brain regions. The study of the effects of acupuncture on brain imaging is not adequately developed, and still needs further improvement and development. The brain function networks associated with acupuncture treatment of depression has not yet been adequately developed to provide a scientific and standardized mechanism of the effects of acupuncture. For this purpose, this paper is analyzing in depth the clinical studies on the treatment of anxiety and depression by acupuncture and moxibustion, by depicting how the employment of the fMRI technology provides significant imaging changes in the brain regions. Thereby the paper also provides reference for future clinical research on the treatment of anxiety and depression.